Physical abilities and morphological variables of International female rugby union players and relationships with match performance variables across five seasons - JAMES COLE (2021)
Purpose: The aim of this study was to examine the relationships between combinations of physical abilities and morphological variables with KPIs and running loads during matches in International rugby union players. Methods: A total of 831 match performances from seventy-six female players, across five competitive seasons, were analysed between 2015 and 2019 using global positioning systems and performance analysis. A total of 309 physical assessments over 33 testing dates were also used for analysis. The relationships between match running and performance analysis variables, and closed testing variables were assessed using linear mixed modelling, with control for positional and season variation. Results: Several relationships were found between match and testing data. Maximal aerobic speed (MAS) had a positive relationship with the number of sprints, total distance, total distance < 3 m·s-1, total distance 3 to 5.5 m·s-1, and total distance > 5.5 m·s-1 performed in games (η2 = 0.31, 0.22, 0.02, 0.14, 0.18, respectively). Countermovement jump (CMJ) was positively associated with all kinematic variables, including: accelerations (η2 = 0.12), decelerations (η2 = 0.09), sprints (η2 = 0.28), total distance (η2 = 0.21), and total distance greater than 5.5 m·s-1 (η2 = 0.26). Skinfolds showed a positive relationship with total distance (η2 = 0.40) and sprints (η2 = 0.34). Sprints also had a negative relationship with 10 m split time (η2 = -0.22). Conclusion: The positive relationship of MAS and CMJ with various on-field work-rate metrics highlight the importance of conditioning both endurance capacity and explosive power to achieve international standards in female rugby union. Skinfold results were unexpected but were attributed to positional variance within the current squad and possible ‘protective’ effects of higher fat mass. The current results suggest that practitioners can potentially improve match-running performance by improving certain physical abilities; namely, CMJ and MAS, irrespective of positional influence, in female rugby union.